Univalent Criteria for Analytic Functions Involving Schwarzian Derivative (Communications in Mathematical Research, 2019)
In this paper, some new criteria for univalence of analytic functions defined in the unit disk in terms of two parameters are presented. Moreover, the relatedresult of Aharonov and Elias (Aharonov D, Elias U. Univalence criteria depending onparameters. $Anal$. $Math$. $Phys$., 2014, 4(1-2): 23–34) is generalized.